Application of microtechnology to elucidate nanotechnology - Chen, Liuying (Nanyang Technological University, 2022)
Engineereed nanoparticles (ENPs) are being used widely for their promising properties. In particular, zinc oxide (ZnO) and titanium dioxide (TiO2) nanoparticles (NPs) are two ENPs commonly found in sunscreen products for their UV absorbing properties. However, concerns have risen regarding the safety of their usage due to possible cytotoxic effects it may induce onto humans. Current methods in determining the cytotoxic levels of these ENPs utilises classic cell culture methods which presents limitations in presenting relevant in-vivo microenvironments. The dynamic complexity of in-situ microenvironment is not fully reflected and hence, there may be disparity in cellular functions and outcomes. By using micropatterning to assess cytotoxicity, an in-depth understanding of the mechanistic pathways of nanoparticles can be unveiled. Our study demonstrates using micropatterning as a tool in determining the cytotoxic effects of surface functionalised ZnO NPs and TiO2 NPs on human dermal keratinocytes (HaCaT cells). In our first study, with the aim of investigating how the cytotoxic response of ENPs is influenced by cell cluster size, circular islands of 50 um and 150 um in diameter were micropatterned before treatment with surface functionalised ZnO NPs. Our results have shown no difference in toxicity outcome though there are differences in mitochondria reactive oxygen species (mROS). This suggests that cellular functions may be impaired without causing cell death. In the second study, to examine how ENPs have an effect on cell chirality, circular islands of 150 um in diameter were treated with ZnO and TiO2 NPs. Our results have shown that ROS generation by both NPs led to an overall decrease in cell velocity, and possible differences in toxic pathway between the two NPs may have led to varying observations in directional sensing of the micropatterned cells.